The Value of Struggle in the Film Ar-Rihlah (The Journey): A Narrative Semiotic Analysis by A. J. Greimas - Siti Hilmiatul Alawiyah; Rohanda; M. Abdul Halim (Raja Zulkarnain Education Foundation, 2025)
This study aims to determine the narrative structure and values of struggle in the film Ar-Rihlah through A. J Greimas' narrative semiotic approach. The method employed is descriptive, utilizing qualitative data. Data on the narrative structure and values of struggle in the film Ar-Rihlah were collected using observation guidelines based on time triangulation, assisted by a checklist, through the process of observing, marking, and recording sentences or dialogues that contain values of struggle. J Greimas' narrative semiotic analysis. Data on narrative structure and values of struggle in the film Ar-Rihlah through a narrative semiotic approach were analyzed through three stages: a) identification of the role of actants; b) mapping of functional structures; c) interpretation of narrative meaning that forms the values of struggle. The results of the study show that the values of struggle in the film Ar-Rihlah (The Journey) are not only expressed in physical combat, but also encompass values such as willingness to sacrifice, unity, respect, patience, and an unyielding spirit. The values of struggle in the film Ar-Rihlah, examined through a narrative semiotic approach, are constructed narratively through the relationship between the actants and the stages of the storyline.